(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2018)
The study of joint binding of intercalating compounds – ethidium bromide (EtBr) and mitoxantrone (MTX) with double-stranded DNA (ds-DNA) and poly(rA)-poly(rU) (ds-RNA) has been carried out by UV-melting method. The melting parameters of the complexes of both EtBr–ds-DNA–MTX and EtBr–ds-RNA–MTX triple systems were obtained. Changes of the melting parameters of these complexes revealed that EtBr binds to both ds-DNA and ds-RNA by several modes, though these binding modes of EtBr with nucleic acids (NA) were performed in the presence of MTX as well. MTX binds to ds-DNA and ds-RNA by semi-intercalation mode although this ligand shows more pronounced affinity to DNA than to RNA. It was found that at the joint binding of both ligands to NA a competition emerges between them and the effect of EtBr on the melting parameters of NA prevails.